Posttraumatic Stress Disorder After Birth: A Metaphor Analysis. Issue 2 (March 2016) - Beck, Cheryl Tatano
Abstract: Purpose: Nine percent of mothers screened positive for meeting the diagnostic criteria for posttraumatic stress disorder (PTSD) due to childbirth in a recent study of childbearing women in the United States. The purpose of this study was to analyze the language used by mothers experiencing PTSD after traumatic birth for metaphors as a rich source of insight into this mental illness for maternal–child nurses. Study Design and Methods: A secondary analysis was conducted of the corpus of 124 typed pages from the primary qualitative study of women's experiences of PTSD following traumatic childbirth. The Pragglejaz Group's metaphor identification procedure was the method used for identifying metaphorically used words in the mothers' discourse. Results: Nine metaphors emerged. These metaphors portray PTSD due to childbirth as a mechanical robot, a ticking time bomb, an invisible wall, a video on constant reply, enveloping darkness, a dangerous ocean, a thief in the night, a bottomless abyss, and suffocating layers of trauma. Clinical Implications: Metaphors that mothers used to describe their experiences of PTSD following a traumatic birth provide rich insight for maternal–child nurses. These metaphors give a new voice to women's experiences of PTSD and are a perfect match for a valuable source for nurses' evidence-based practice. Abstract : Nine percent of mothers screened positive for meeting the diagnostic criteria for Posttraumatic Stress Disorder (PTSD) due to childbirth in a recent study of childbearing women in the United States. The purpose of this study was to analyze the language used by mothers experiencing PTSD after traumatic birth for metaphors as a rich source of insight into this mental illness for maternal child nurses.